Créer contre l’oubli ou la censure de la mémoire uruguayenne - Dorothée Chouitem (Les Cahiers de Framespa)
During its last dictatorship the murgas, like all forms of artistic entertainment, were closely monitored by a state-controlled censorship. After the 1984 elections, the Uruguayan dictatorship came into demise when the Colorado Party claimed victory. In this more permissive democratic environment, murgas had claimed, by 1985, an important place in the Uruguayan entertainment stages, celebrating its long-lost liberties. If the immediate social context influences murga productions, how can a new way of communication, in theory without political controls, reflect current historic structures? How can the binomial memory vs silence be crystallized in artistic productions? How did the murga, through its government-subsidized entertainment productions, contravene a legal framework whose main objective was to dilute the Uruguayan collective memory and promote silence ?